SINTESIS PIRAZOLIN DARI KALKON 3-KLORO INTI NAFTALEN DAN UJI AKTIVITASNYA SEBAGAI ANTIBAKTERI - Ary Puspita; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazolines have been reported to possess many of interesting biological activities such as antimicrobial, antidepressant, antitumor, antioxidant, antiinflammatory, anticancer and anticonvulsant activity . In this research, a compound of 1-phenyl-3-(2-naphthyl)-5-(3-chlorophenyl)-2-pyrazoline was synthesized by cyclization of (E)-3-(3-chlorophenyl)-1-naphthalene-2-yl-prop-2-en-1-on and phenylhydrazine using glacial acetic acid as a catalyst under microwave irradiation. The compound showed a good yield and it was characterized by UV, IR, 1 H-NMR and 13 C-NMR spectroscopy. The antibacterial activity of this compound was determined using agar diffusion method against Gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram negative bacteria (Escherichia coli and Salmonella typhi). The compound showed very poor activity against Salmonella typhi.